The effect of privatization on general Revenues of State Budget Comparative Study - إبراهيم رباب خليل; عبدالقادر بان صلاح (Journal of Legal Sciences, 2021)
The major countries have a lot of financial burdens as a result of their public expenditure to run their public facilities and implement their obligations in this regard. Countries may need to maximize their public revenues to meet their expenditures and increase the privatization policy according to the legal concept of selling their facilities or public companies. That the public revenues of the state and the shortcomings of the view of the pro-privatization as a means to increase the financial revenues of the state and the loss suffered by the States because of the fertility of its facilities and companies to the public and especially the elites of them because it will deprive them of the revenue fixed constant It flows into the state budget financial resources that are on-going need.